Spectral Signatures of Ultrafast Spin Crossover in Single Crystal [FeII(bpy)3](PF6)2. Issue 15 (25th February 2016) - Field, Ryan; Liu, Lai Chung; Gawelda, Wojciech; Lu, Cheng; Miller, R. J. Dwayne
Abstract: Solvated iron(II)‐tris(bipyridine) ([Fe II (bpy)3 ] 2+ ) has been extensively studied with regard to the spin crossover (SCO) phenomenon. Herein, the ultrafast spin transition dynamics of single crystal [Fe II (bpy)3 ](PF6 )2 was characterized for the first time using femtosecond transient absorption (TA) spectroscopy. The single crystal environment is of interest for experiments that probe the nuclear motions involved in the SCO transition, such as femtosecond X‐ray and electron diffraction. We found that the TA at early times is very similar to what has been reported in solvated [Fe II (bpy)3 ] 2+, whereas the later dynamics are perturbed in the crystal environment. The lifetime of the high‐spin state is found to be much shorter (100 ps) than in solution due to chemical pressure exerted by the lattice. Oscillatory behavior was observed on both time scales. Our results show that single crystal [Fe II (bpy)3 ](PF6 )2 serves as an excellent model system for localized molecular spin transitions. Abstract : Jumping spin : For the first time, the spectral signatures associated with spin crossover in single crystal [Fe II (bpy)3 ](PF6 )2 (see figure) with detection in real time are reported. The ultrafast dynamics was found to be very similar to that previously reported in the solvated case, whereas dynamics at later times is significantly perturbed in the crystal environment.